1989
DOI: 10.1530/acta.0.1210067
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine abnormalities in patients with adrenal tumours incidentally discovered on computed tomography

Abstract: Abstract. To determine endocrine activity of adrenal tumours incidentally discovered on CT, we examined 20 consecutive patients. They underwent thorough hormonal assessment and scintigraphic scanning with radioactive cholesterol under dexamethasone suppression (19 patients). Biochemical findings compatible with cortisol hypersecretion were detected in 5 patients. One patient had reduced reserves of cortisol secretion and one had hyporeninemic hypoaldosteronism. The scintigraphy showed no uptake in 10, unilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 0 publications
4
25
0
Order By: Relevance
“…Some patients with normal hormonal function also showed mass enlargement and, in this respect, the possible risk of malignant transformation must always be considered. Many studies have suggested that the likelihood of malignant transformation at long-term follow-up is very small (14,17,19,20). We observed a conspicuous mass increase in one woman 6 months after diagnosis: adrenalectomy was performed to remove the lesion, which was identified as a primary non-Hodgkin's lymphoma.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Some patients with normal hormonal function also showed mass enlargement and, in this respect, the possible risk of malignant transformation must always be considered. Many studies have suggested that the likelihood of malignant transformation at long-term follow-up is very small (14,17,19,20). We observed a conspicuous mass increase in one woman 6 months after diagnosis: adrenalectomy was performed to remove the lesion, which was identified as a primary non-Hodgkin's lymphoma.…”
Section: Discussionmentioning
confidence: 72%
“…We found an enlargement $ 1 cm in 20% of the cases, similar to two previous investigations (14,15) that reported an increase in tumor size in 17% and 15% of patients respectively. No mass enlargement was observed in two other small studies (17,18) while, in larger series, tumor growth was detected in a very low percentage of cases (3.3 -4.3%) (19,20). However, in one of these studies (20), the investigators obtained only indirect data from office records, or by telephone or mail contacts for most patients.…”
Section: Discussionmentioning
confidence: 96%
“…4 Most studies evaluating the natural history and long-term outcome of AIs were small and retrospective. [171][172][173][174][175][176][177][178][179] A multicenter Swedish prospective study involving 229 patients with AIs with a median follow-up period of 25 months (range 3-108 months) demonstrated an increase in size of ≥0.5 cm in 7.4% The percentage of AIs developing hyperfunction during follow-up is generally low (about 1.7%), ranging from 0 to 11%. 4 Indeed, the vast majority of studies demonstrated no hormonal alteration during follow-up.…”
Section: Natural History and Follow-up Strategymentioning
confidence: 99%
“…4 Indeed, the vast majority of studies demonstrated no hormonal alteration during follow-up. [173][174][175][176]178,179 The most common disorder observed is SCS, whereas catecholamine and ALD hypersecretion appear to be extremely rare. [1][2][3][4]172,177,180 The progression from SCS to overt disease is controversial.…”
Section: Natural History and Follow-up Strategymentioning
confidence: 99%
“…These so-called "adrenal incidentalomas" are usually asymptomatic and often classified as non-functional tumors, but in recent years there have been several case reports of asymptomatic cortisol producing adrenal adenoma (ASCA) which secretes cortisol without clinical evidence of Cushing's syndrome, the so-called "Pre-Cushing's syndrome" or "Preclinical Cushing's syndrome" [12][13][14][15][16][17][18][19][20][21]. Some cases with incidentaloma were reported to have had adrenocortical insufficiency after removal of the adrenal tumor [17,20].…”
Section: Incidentalmentioning
confidence: 99%